2020
DOI: 10.1093/ofid/ofaa424
|View full text |Cite
|
Sign up to set email alerts
|

Occult Colonic Perforation in a Patient With Coronavirus Disease 2019 After Interleukin-6 Receptor Antagonist Therapy

Abstract: Interleukin-6 blockade (IL-6) has become a focus of therapeutic investigation for the coronavirus-2019 (COVID-19). We report a case of a 34 year-old with COVID-19 pneumonia receiving an IL-6 receptor antagonist (IL-6Ra) who developed spontaneous colonic perforation. This perforation occurred despite a benign abdominal exam and in the absence of other known risk factors associated with colonic perforation. Examination of the colon by electron microscopy revealed numerous intact SARS-CoV-2 virions abutting the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…He got occult colonic perforation following interleukin -6 receptor antagonist therapy. They identifi ed SARS-CoV-2 virions in the colon by electron microscopy [8]. In their description, abdominal examination did not reveal features of peritonitis i.e., similar to initial fi ndings of our case.…”
Section: Severalsupporting
confidence: 78%
“…He got occult colonic perforation following interleukin -6 receptor antagonist therapy. They identifi ed SARS-CoV-2 virions in the colon by electron microscopy [8]. In their description, abdominal examination did not reveal features of peritonitis i.e., similar to initial fi ndings of our case.…”
Section: Severalsupporting
confidence: 78%
“…Both patients underwent right hemicolectomy, and one of them required ileostomy. However, both patients survived [16] , [17] . Corrêa et al describe an 80-year-old patient with COVID-19 who presented with acute respiratory and gastrointestinal manifestations.…”
Section: Discussionmentioning
confidence: 92%
“…Treatment in these cases must be surgical. Most of the reported cases of colonic perforation in critically ill patients with COVID-19 have been managed with colectomy [14] , [15] , [16] , [17] , [18] . De Nardi et al reported a 53-year-old patient with COVID-19 infection who had a perforation in the ascending colon during his hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of colonic perforation varies, including colonic pseudo-obstruction, diverticulitis, stercoral perforation and medication-induced perforation. In COVID-19 cases, colonic perforation caused by interleukin-6 receptor antagonist therapy was also reported [ 14 ]. However, in the present case, these causes were unlikely based on the radiological and surgical findings.…”
Section: Discussionmentioning
confidence: 99%